The Effects of Mycotoxins, Toxin Binder and Deactivator on the Hematology, Serum Chemistry and Immune Response of Broiler Chickens Vaccinated Against Newcastle Disease - Eze, Chekwube Paul; Shoyinka, Vincent Olu.; Ezema, Wilfred Sunday; Chah, Kennedy Foinkfu; Mgbeahuruike, Anthony Christian; Eze, Emmanuel Aniebonam; Ogbonna, Innocent Okonkwo; Suzzy Udeh, Adaeze; Obih, Chosen Ekene (International Journal of Poultry Science, 2025)
Objectives: This study was designed to investigate the effects of mycotoxins and toxin binder and deactivator on the hematology, serum chemistry and immune response of broiler chickens vaccinated against Newcastle disease. Materials and Methods: The finisher feed was moistened with water, and stored in bags for 21 days. It was divided into three parts: A, B, and C. Part A and part B was treated with toxin binder (Toxorid®) and deactivator (Zerotox®) respectively. Part C was not treated with toxin binder or deactivator. The contaminated feeds were stored at 25-30°C for 2 weeks before use. Fresh uncontaminated and untreated feed, ‘D’ served as the positive control and all evaluated for fungal growth and mycotoxins. A total of 224 broilers were used in this study. Broilers of 5-weeks old were divided into eight groups and fed experimental finisher feeds (A, B, C, D). Two weeks Post Exposure (PE), groups AK, BK, CK and DK were revaccinated with ND vaccine (Komarov®). The hematocrit, erythrocyte counts, hemoglobin concentration, mean corpuscular volume, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration of groups A, B, C and D were ascertained. The total and differential leukogram of groups A, B, C and D were determined. The Aspartate Aminotransferase (AST) activity, uric acid, total serum protein, serum albumin and serum globulin concentrations of groups A, B, C and D were determined. The HI titers of all the groups were obtained. The data obtained were subjected to Analysis of Variance (ANOVA). Results: The phenotypic characterization, DNA extraction and Polymerase Chain Reaction (PCR) amplification of the feed samples revealed that the isolates recovered from groups A, B, C and D were mycotoxigenic fungi. The mean total aflatoxins detected via competitive ELISA were 1.25 ppb for A, 0.97 ppb for B, 2.14 ppb for C and 0.73 ppb for D. The hemoglobin and mean corpuscular hemoglobin concentration of group D, at week 9 of age, was significantly (p<0.05) higher than C, but not (p>0.05) significant with A and B. There was significant increase in (p<0.05) leukocyte counts in groups C, A and B when compared with the control group (D) between weeks 2-4 PE. In the differential leukogram, (p<0.05) marked heterophils, eosinophils, monocytes and lymphocytes were seen in groups C, A and B when compared with D between weeks 2-4 PE. Uric acid concentrations of group C at week 2 PE (2.35±0.38) was significantly lower (p<0.05) than those of D (3.58±0.60), B (7.01±2.24) and A (4.17±0.47). The total serum protein and the serum albumin concentrations of group C was significantly (p<0.05) lower than, A and B, at week 4 PE. The serum globulin and serum albumin globulin ratio concentrations presented the same pattern as seen above. The HI titres of the revaccinated groups, (AK, BK, CK and DK) increased (p<0.05) significantly when compared with groups A, B, C and D between weeks 3-5 PE. Conclusion: The emanating hematological, HI titers, and biochemical lesions observed among the exposed groups indicated the extent of systemic damage by mycotoxins and ameliorating effects of binders in salvaging contaminated feed. This research outcome is a useful guide to policy formulators, farmers, nutritionists and researchers.